Некоторые особенноcти восприятия литовских мягких согласных носителями русского языка - Балшайтите, Д. (Kalbotyra, 1986)
In the article the results of the experiments on the perception of the Lithuanian palatalized apical consonants by Russian speakers are described. The analysis of the data permits us to reveal the perceptional features of the Lithuanian palatalized consonants, to determine more favourable positions for the distinction of their palatalization. The perception of the palatalization of the consonant depends upon the quality of the following vowel. The aperture and the length of the following vowel are the most important things for the perception of the palatalization of the lithuanian consonants.